2018
DOI: 10.1039/c8cp01907j
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced proton transfer inside an engineered green fluorescent protein: a stepwise–concerted-hybrid reaction

Abstract: Photoactivated proton transfer (PT) wire is responsible for the glow of green fluorescent protein (GFP), which is crucial for bioimaging and biomedicine. In this work, a new GFP-S65T/S205V double mutant is developed from wild-type GFP in which the PT wire is significantly modified. We implement femtosecond transient absorption (fs-TA) and femtosecond stimulated Raman spectroscopy (FSRS) to delineate the PT process in action. The excited state proton transfer proceeds on the ∼110 ps timescale, which infers that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 49 publications
1
29
0
Order By: Relevance
“…The kinetic model for transient molecular species and the match between experimental and fitted traces across the spectral detection window at four representative time delay points are shown in Figure S1 (see the Supplementary Materials ). Previous studies on related proteins have shown that a purely concerted model does not fit the TA spectra well, and some preparation stages typically exist before the main ESPT reaction step [ 21 , 26 ]. The resultant evolution-associated spectra (EAS) are plotted in Figure 2 b with a root-mean-square (RMS) value of 1.318 × 10 −3 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The kinetic model for transient molecular species and the match between experimental and fitted traces across the spectral detection window at four representative time delay points are shown in Figure S1 (see the Supplementary Materials ). Previous studies on related proteins have shown that a purely concerted model does not fit the TA spectra well, and some preparation stages typically exist before the main ESPT reaction step [ 21 , 26 ]. The resultant evolution-associated spectra (EAS) are plotted in Figure 2 b with a root-mean-square (RMS) value of 1.318 × 10 −3 .…”
Section: Resultsmentioning
confidence: 99%
“…The small emission peak at 512 nm is likely from the fluorescence background (because it is present to a certain extent at negative time delay points) or some ultrafast ESPT channel via those pre-existing, largely optimal H-bonding chains [ 29 , 32 , 45 ]. The initial EAS then evolves to the second EAS with a time constant of 3.8 ps, during which the intensity of the A* SE band near 478 nm increases, indicating the necessity of a preparation stage before the ESPT process [ 4 , 21 , 26 , 46 ]. The ESA band below 450 nm also blue shifts, suggesting that the A* S 1 state is stabilized on this time scale.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations